How teachers handle difficult situations and the emotions they raise (Revista Contexto & Educação, 2025)
The purpose of this research is understanding the situations that trigger negative-valence emotions in the daily praxis of professors in the field of Applied Social Sciences and how these emotions are overcome. Using the critical incident technique, 24 higher education professors in the field of Applied Social Sciences were interviewed. Fear arises in situations related to dismissal, violence, the unknown, and peer judgment. Anger, on the other hand, is less frequent and emerges in situations of unmet expectations. To manage these situations, the professors sought options available in their repertoire of knowledge, acquired through teacher training, experience in other fields, or from their peers. Finally, it can be inferred from the results that professors are, above all, human beings, and knowing how to deal with their own emotions is not a minor issue in teacher education.
Keywords: Emotions; regulation of emotions; teacher training